2020
DOI: 10.4049/jimmunol.1900941
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Preterm Infants Have Significant Alterations in Their Conventional T Cell Compartment during the First Weeks of Life

Abstract: Extremely preterm neonates are particularly susceptible to infections, likely because of severely impaired immune function. However, little is known on the composition of the T cell compartment in early life in this vulnerable population. We conducted a comprehensive phenotypic flow cytometry-based longitudinal analysis of the peripheral conventional T cell compartment of human extremely low gestational age neonates (ELGAN) with extremely low birth weight (ELBW; <1000 g) participating in a randomized placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 55 publications
(55 reference statements)
4
22
1
Order By: Relevance
“…This observed limited T cell response may be attributed to the limited expansion and differentiation of T cells, including regulatory T cells, in neonatal mice ( 55 , 56 ). Notably, immaturity of the T cell compartment is also observed in extremely preterm human infants, increasing their susceptibility to infection and impairing their immune functions, which may predispose them to NEC development ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…This observed limited T cell response may be attributed to the limited expansion and differentiation of T cells, including regulatory T cells, in neonatal mice ( 55 , 56 ). Notably, immaturity of the T cell compartment is also observed in extremely preterm human infants, increasing their susceptibility to infection and impairing their immune functions, which may predispose them to NEC development ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…, blood, lymphoid, and mucosal tissues) has been underexplored. Tregs likely regulate appropriate local mucosal immune responses during microbial colonization, as Tregs may protect against necrotizing enterocolitis in preterm infants by promoting tolerance during newborn gut microbial colonization ( 46 ). Because the immunosuppressive effects of these Tregs may increase infectious disease susceptibility and could dampen vaccine responsiveness in infancy, further research is crucial to gain a deeper understanding of their abundance and function in early life.…”
Section: T Cells In Early Lifementioning
confidence: 99%
“…There are several features of preterm T cells which limit their function. First, preterm neonates have been found to have marked lymphopenia (up to 50% reduction) with a significant decrease in the percentage of total, CD4 + , and CD8 + lymphocytes compared with full term infants (121). The reduction is most notable among the CD8 + population, resulting in an increased CD4/CD8 ratio.…”
Section: T Cellsmentioning
confidence: 99%
“…The transcription factors T-bet, GATA3, and RORγt, regulate differentiation into Th1, Th2, and Th17 phenotypes, respectively. Accordingly, recent studies have shown that the proportion of T-bet expressing CD4 + T cells is reduced within the preterm T cell population (121).…”
Section: T Cellsmentioning
confidence: 99%